Understanding the impact of working conditions on ranger vulnerability to corruption: insights from a global survey - Lebon, Héloïse; Singh, Rohit; Abdulla, Amal Fathima; Ahmed, Kaleem; Aisha, Hamera (Frontiers in Conservation Science, 2024)
Rangers play a crucial role on the frontline of conservation; however, they often face difficult and sometimes dangerous working conditions, along with inadequate pay, equipment, training, and recognition. This study aims to determine the influence of rangers’ working conditions on their vulnerability to corruption using correlation analysis. The research utilized the Global Ranger Perception Survey 2019 dataset, a global-scale survey that collected responses from 6,101 rangers across 25 countries on various aspects of their working conditions. We further analyzed the results by gender and geographic region. Key findings indicate that women have a lower propensity to engage in corrupt activities. Conversely, at the regional level, Latin America demonstrates a heightened susceptibility to corruption compared to other regions. Additionally, there is a strong correlation between corruption and certain aspects of rangers’ working conditions in Latin America. Future assessments, such as the State of the Ranger Report, could provide a monitoring mechanism to evaluate the long-term effects of improvements in rangers' working conditions and their potential vulnerability to corruption worldwide. Country-specific or even landscape-specific in-depth studies would be valuable for developing targeted strategies to address corruption within the workforce while also improving rangers’ working conditions.